On disjunctive dependencies - Ignacio Bosque (Universitat Autònoma de Barcelona, 2010)
This paper argues that some Spanish syntactic structures contain lexically selected null wh- disjunctive operators, and that a number of apparent subordinate declarative clauses turn out to be hidden indirect questions. It also argues that these operators appear in sentential adjuncts as well, giving rise to a variety of so-called unconditional structures. It is shown that disjunctive phrases in structures with selected and unselected null wh- operators are subject to similar locality conditions. In the final section, new arguments are presented in favour of analyzing disjunctive expressions as a variant of free-choice phrases in certain contexts.